Mastering Microsoft Visual Basic 2005 - Petroutsos, Evangelos (Wiley Pub., 2006)
This book offers expert assistance that makes it even easier. Inside, two veteran Visual Basic developers show you how to do everything Express Edition makes possible--and even a few things, such as Office development.